Comparative efficiency of two cover crops on soil enrichment, accumulation of nutrients, microbial population and growth of Hevea brasiliensis in Meghalaya - Singh R P; Chaudhuri D; Deka H K (Natural Rubber Research, 2007)
A field experiment conducted in a rubber grower's field near Jorabar, Ribhoi district of Meghalaya, indicated that growing leguminous cover crops, Pueraria phaseoloides and Mucuna bracteata, in the immature phase of rubber improved the fertility status of soil, microbial population, soil moisture content, nutrient content in litter and growth of Hevea brasiliensis. Establishment of M. bracteata by sowing the treated seeds in patches (1 m2) registered higher organic carbon status, microbial population, soil moisture content and growth of young H. brasiliensis than other methods of its establishment or P. phaseoloides established by different methods.
Source Year: 2007
Keywords: Cover crops; Cover crops; Litter; Litter; Microbial population; Microbial population; Mucuna bracteata; Mucuna bracteata; Nutrients; Nutrients; Pueraria phaseoloides; Pueraria phaseoloides